Holocene loess in the Himalayas piedmont of southeastern Nepal - Latrubesse, Edgardo M. (2024)
Loess, loess-like, sandy loess, and sandy-silty fluvial–aeolian deposits are intercalated to fluvial sediments and lie on a flat surface under intense agricultural land use in Bardibas, Mahottari district, central Nepal. To identify the depositional processes and provenance, we carried out geochemical, mineralogical, SEM, and grain-size analyses. Optically stimulated luminescence (OSL) dating shows the aeolian deposits are from the late Holocene (1.0–4.8 ka). Our results demonstrate that the loess and loess-like deposits (i) were dominantly sourced locally from deflation Quaternary sediments of the Terai Plain; (ii) are related to the composition of Siwalik rocks; and (iii) were deposited during dry periods of weak activity of the Indian Summer Monsoon.